Genetic Diversity of Montenegrin Local Sheep Breeds Based on Microsatellite Markers - Milan Marković; Dušica Radonjić; Minja Zorc; Milena Đokić; Božidarka Marković (Animals, 2022)
The Montenegrin sheep population mostly consists of local breeds and their crossbreeds that are very valuable from their genome preservation point of view. The aim of this study was the investigation of the genetic diversity of seven Montenegrin sheep breeds (Jezeropivska—JP, Sora—SOR, Zetska zuja—ZZ, Bardoka—BAR, Sjenička—SJ, Ljaba—Lj, and Piperska zuja—PIP) using 18 microsatellite sets of markers. The genotyping was done for 291 samples from seven populations using the multiplex amplification of sequences with polymerase chain reaction (PCR). The parameters of genetic diversity were estimated using several software tools. In total, 243 alleles were found, with a range of 6 to 25 by locus. The mean observed heterozygosity (Ho), polymorphism information content (PIC), and Fis values (fixation index) per marker were 0.728, 0.781, and −0.007, respectively. The mean number of alleles per breed varied from 4.889 in ZZ to 10.056 in JP. The highest Ho was estimated for JP (0.763) and the lowest for ZZ (0.640). The genetic structure showed close relations between SOR and JP, and both of them with SJ, while ZZ, LJ, and PIP were more distanced. This study provides useful indicators for the development of further in-depth studies and the creation of appropriate conservation programs.